MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN - Khabib Sharifudin; Andri Arfiyanto, Miftahul Huda, Mufasirul Bayani (CV. ADIBA AISHA AMIRA, 2024)
Educational facilities and infrastructure are important resources in supporting the achievement of educational goals. The availability of adequate facilities and infrastructure needs to be supported by appropriate management of educational facilities and infrastructure. This article aims to describe and analyze the management of educational facilities and infrastructure. What this article uses in writing is library research. Data collection through various sources from books, articles or journals, and the results of previous research. Educational facilities and infrastructure are needed to support the teaching and learning process directly and indirectly. in the management of educational facilities and infrastructure, it is hoped that it can provide adequate educational facilities and infrastructure in both state and private schools.